Tax Policy and Aggregate Demand Management Under Catching Up with the Joneses - Ljungqvist, Lars; Uhlig, Harald (American Economic Review, 2000)
This paper examines the role for tax policies in productivity-shock driven economies with catching-up-with-the-Joneses utility functions. The optimal tax policy is shown to affect the economy countercyclically via procyclical taxes, i.e., “cooling down” the economy with higher taxes when it is “overheating” in booms and “stimulating” the economy with lower taxes in recessions to keep consumption up. Thus, models with catching-up-with-the-Joneses utility functions call for traditional Keynesian demand-management policies but for rather unorthodox reasons. (JEL E21, E62, E63)